2022
DOI: 10.1177/21582440211069143
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Anxiety and Individualism-Collectivism Culture: A Top-Down Approach for a Country/Regional-Level Analysis

Abstract: This study explored how foreign language anxiety in class relates to individualism-collectivism culture. Additionally, to serve as a guideline for foreign language anxiety assessment, the study determined a normative score of the Foreign Language Classroom Anxiety Scale (FLCAS), which is well known and frequently applied for foreign language anxiety examination. After conducting a literature search identifying 106 studies in 35 countries/regions, a top-down approach was used to analyze aggregate FLCAS mean sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 118 publications
0
8
0
Order By: Relevance
“…In fact, feeling of tension, apprehension, fearfulness, and worry in language class, which had been pointed to greatly influence e-learner's progress in mastering the target language, are all critical factors that limit the usefulness of e-learning (Tuti, 2018) Linguistic anxiety can be defined as a cognitive state that occurs during the use of a second language, resulting in a deficit in linguistic communication. This state of anxiety involves three related states that become evident during performance, which are perceptual communicative anxiety, experimental anxiety and fear of negative evaluation (Toyama and Yamazaki, 2022). Communication Perception Anxiety is a type of shyness, which is accompanied by fear or anxiety about communicating with people, and it manifests itself in several manifestations, including difficulty speaking in groups or difficulty making a speech, or difficulty listening to or learning a verbal message (Chen, 2019).Experimental anxiety is a type of cognitive anxiety that arises from a fear of failure, such as becoming apprehensive about the consequences of insufficient performance during a particular test or assessment (Zuardi, Crippa, Hallak and Gorayeb, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, feeling of tension, apprehension, fearfulness, and worry in language class, which had been pointed to greatly influence e-learner's progress in mastering the target language, are all critical factors that limit the usefulness of e-learning (Tuti, 2018) Linguistic anxiety can be defined as a cognitive state that occurs during the use of a second language, resulting in a deficit in linguistic communication. This state of anxiety involves three related states that become evident during performance, which are perceptual communicative anxiety, experimental anxiety and fear of negative evaluation (Toyama and Yamazaki, 2022). Communication Perception Anxiety is a type of shyness, which is accompanied by fear or anxiety about communicating with people, and it manifests itself in several manifestations, including difficulty speaking in groups or difficulty making a speech, or difficulty listening to or learning a verbal message (Chen, 2019).Experimental anxiety is a type of cognitive anxiety that arises from a fear of failure, such as becoming apprehensive about the consequences of insufficient performance during a particular test or assessment (Zuardi, Crippa, Hallak and Gorayeb, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, as Horwitz (2001) proposes, language anxiety may “vary in different cultural groups” (p. 116) and this anxiety “has different triggers and manifestations in different cultures” (Horwitz, 2016, p. 71). This proposition was partially supported in Toyama and Yamazaki’s (2022) study of the relationship between language anxiety and culture. Based on the FLCAS scores and the ratings of Hofstede’s (Hofstede et al, 2010) individualism-collectivism cultural dimensions, Toyama and Yamazaki reported a significant relationship for higher education institutions.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, there seemed to be more variation among the correlations in the three studies than in Horwitz’s (1986) validation study, which found the general language classroom anxiety scores (as measured by the FLCAS ) to show a similar relationship with Spanish ( r =−.49) and French ( r =−.54) final grades. Horwitz’s finding bears relevance to Toyama and Yamazaki’s (2022) investigation of how individualism-collectivism culture relates to language anxiety. Toyama and Yamazaki identified 106 studies in 35 countries/regions and did not find a significant relationship between culture and language anxiety for all educational institutions and elementary to high schools.…”
Section: Language Anxiety: Stability Variabilityand Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural differences can cause language anxiety. In most research, speaking anxiety in relation to cultural differences stems from, one of them, different accepted cultural thoughts (Toyama & Yamazaki, 2022). Tseng (2012) asserts that the more unfamiliar the students to the culture of target language, the more they experience anxiety in the target language as the cultural background of speaker and the cultural background of target language can be very different, such as the using of vocabularies.…”
Section: Introductionmentioning
confidence: 99%